(untitled) (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
Introduction: In adolescence nutritional conditions are very important to support their growth and development. Nutrition problems that usually occur in adolescents are caused by several factors such as the level of nutritional knowledge that will affect their behavior and lifestyle such as sedentary activity, screen time duration, and also sleep duration especially for adolescent who attend school in islamic boarding school. Purpose: This study aims to know the description of sedentary lifestyle which includes sedentary activity and sleep duration of adolescent girls in Islamic Boarding School Darul Aman Gombara Makassar. Materials and Methods: The type of this study is descriptive. The sample of this study was 96 adolescents using total sampling. Collecting data for sedentary activity using the recall activity questionnaire, and for the sleep duration using STQ (Sleep Timing Questionnaire). Data pricessing and analysis in this study using SPSS. Result: The results of the analysis for sedentary activity found that 27,1% of respondents sedentary, and 72,9% of respondents not sedentary. As for sleep duration on